Evaluation of Cefotaxime and Desacetylcefotaxime Concentrations in Cord Blood after Intrapartum Prophylaxis with Cefotaxime - Lepercq, Jacques (American Society for Microbiology (ASM), 2009)
Preterm premature rupture of the membranes is associated with a high risk of neonatal sepsis. An increase in the incidence of early-onset neonatal sepsis due to ampicillin-resistant Escherichia coli in premature infants has been observed in the past few years. Intrapartum prophylaxis with ampicillin has proven to be efficient for the prevention of early neonatal sepsis due to group B streptococci. To date, there is no strategy for the prevention of early neonatal sepsis due to ampicillin-resistant E. coli. Our aim was to investigate whether a standardized dosage regimen of intrapartum cefotaxime could provide concentrations in the cord blood greater than the cefotaxime MIC(90) for E. coli. Seven pregnant women hospitalized with preterm premature rupture of the membranes and colonized with ampicillin-resistant isolates of the family Enterobacteriaceae were included. Cefotaxime was given intravenously during delivery, as follows: 2 g at the onset of labor and then 1 g every 4 h until delivery. Blood specimens were collected from the mother 30 min after the first injection and just before the second injection, and at birth, blood specimens were simultaneously collected from the mother and the umbilical cord. The concentrations of cefotaxime in the cord blood ranged from 0.5 to 8.5 mg/liter. The MIC(90) of cefotaxime for E. coli strains (0.125 mg/liter) was achieved in all cases. This preliminary study supports the use of cefotaxime for intrapartum prophylaxis in women colonized with ampicillin-resistant isolates of Enterobacteriaceae. The effectiveness of this regimen for the prevention of neonatal sepsis needs to be evaluated with a larger population.